2023
DOI: 10.3847/1538-4357/acc9ae
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Origins of the Near-resonant Kepler Planets

Abstract: Short-period super-Earths and mini-Neptunes encircle more than ∼50% of Sun-like stars and are relatively amenable to direct observational characterization. Despite this, environments in which these planets accrete are difficult to probe directly. Nevertheless, pairs of planets that are close to orbital resonances provide a unique window into the inner regions of protoplanetary disks, as they preserve the conditions of their formation, as well as the early evolution of their orbital architectures. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…In this work, we study 20 systems and 36 resonances that overlap with Goldberg & Batygin (2023). Of these systems, we confirm 40% of resonances that they also confirm.…”
Section: Confirming Resonances Using Librationsupporting
confidence: 63%
See 1 more Smart Citation
“…In this work, we study 20 systems and 36 resonances that overlap with Goldberg & Batygin (2023). Of these systems, we confirm 40% of resonances that they also confirm.…”
Section: Confirming Resonances Using Librationsupporting
confidence: 63%
“…There are numerous other ways to study and confirm MMRs, including verifying that the system lies within the separatrix of the system's phase space (Winter & Murray 1997). Our methods rely entirely on the libration of the resonant angles, and recent studies have suggested this technique might not be completely accurate; Goldberg & Batygin (2023) found that many TTV systems might show librating angles, even if the system is formally nonresonant because the Hamiltonian has no separatrix.…”
Section: Confirming Resonances Using Librationmentioning
confidence: 99%
“…However, as encountered in the case of the turbulent disk model, this formalism alone may not suffice as a global framework for the evolution of multiple-planet systems. The postnebular instabilities characteristic of this model are expected to occur efficiently and near-ubiquitously (Ghosh & Chatterjee 2023;Lammers et al 2023) such that only a few percent of systems would be expected to retain their initial resonant signatures (Goldberg & Batygin 2023), which lies in direct tension with the observed occurrence of near-resonant planetary configurations. While the achievement of nearresonant structures in such a formalism could thus occur primarily by chance following the epoch of instability (Goldberg & Batygin 2023), such near-resonant pairs would lose memory of their primoridal uniformity and lack any means of subsequent coordination in planetary size, disallowing the prospect of enhanced size uniformity altogether.…”
Section: Postnebular Dynamical Instabilities: Violent Disruption Of Mmrmentioning
confidence: 97%
“…Recent work by Goldberg & Batygin (2023) has demonstrated that, of these various paradigms, the turbulent disk model is particularly amenable to reproducing the properties of observed planetary configurations, as it provides energy dissipation sufficient to reproduce the aforementioned degree of broadened spacing while simultaneously introducing stochastic forces that excite the mixed resonance angles into circulation, thereby successfully dislodging planets from MMR on both accounts. In consideration of planetary pairs within such a disk, we note that, since the provision of nearly equal masses constitutes a stable and energetically optimal configuration for a two-planet system (Adams et al 2020a(Adams et al , 2020b, it reasons that invariance to such stochastic perturbations may itself scale with planetary uniformity as well, such that highly uniform pairs may have a greater tendency to retain their orbital spacing while less uniform pairs may drift farther from MMR (Adams et al 2020b), where subsequent secular interactions between pairs significantly dislodged from MMR may further sculpt their orbital evolution.…”
Section: Turbulent Disk Migration: Quiescent Disruption Of Mmrmentioning
confidence: 99%
See 1 more Smart Citation